2011
DOI: 10.3109/0167482x.2011.626092
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative experience during childbirth

Abstract: Dissociative experiences can occur during childbirth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 25 publications
0
23
0
Order By: Relevance
“…This result corroborate the literature. Indeed, although the assessment of perinatal dissociation during premature childbirth is a rarity in the literature, prematurity has emerged as a significant predictive factor of perinatal dissociation in studies of heterogeneous populations of parturient women [17]. In fact, during a premature birth, cognitive appraisal of preterm labor as unmanageable, negative emotions, feelings of helplessness, fear of death or loss of control and fear of receiving bad news can lead to significant emotional distress, which parturient women attempt to escape by dissociative symptoms [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result corroborate the literature. Indeed, although the assessment of perinatal dissociation during premature childbirth is a rarity in the literature, prematurity has emerged as a significant predictive factor of perinatal dissociation in studies of heterogeneous populations of parturient women [17]. In fact, during a premature birth, cognitive appraisal of preterm labor as unmanageable, negative emotions, feelings of helplessness, fear of death or loss of control and fear of receiving bad news can lead to significant emotional distress, which parturient women attempt to escape by dissociative symptoms [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, Zambaldi et al [17] reported that the occurrence of medical complications for the mother or her child at the time of delivery significantly contributes to the development of perinatal dissociation. The most implicated medical complications in this study were low birth weight, respiratory problems, infections and neonatal jaundice.…”
Section: Discussionmentioning
confidence: 99%
“…4 In our case, onset of depersonalization was 72hrs post partum but the patient orientation was not affected. Somer Eli et al 3 review indicated that depersonalization symptoms can occur in medical condition especially neurological for instance migraine and epilepsy and psychiatric morbidities including depression, panic disorder, post traumatic stress disorder, schizophrenia and stress.…”
Section: Discussionmentioning
confidence: 46%
“…It has been found to be a powerful predictor of trauma (Zambaldi et al, 2011). The Peritraumatic Dissociative Experiences Questionnaire self-report version (PDEQ-SRV) consists of 10 items describing dissociative experiences during the occurrence of a traumatic event.…”
Section: Methodsmentioning
confidence: 99%